(untitled) (Profetik: Jurnal Komunikasi, 2020)
Pekanbaru is the capital city of Riau Province in Indonesia which is known for its progressive trading that made it into a multi-ethnic city. Accordingly, the most ethnic group in Pekanbaru city is the Minangkabau with 40.96% of the total population, followed by Malays who are the native of Riau province, then Javanese, Batak, and Chinese. There is an interesting phenomenon related to youth self-concept from Minangkabau (Minang) as the majority tribe who don’t acknowledge themselves as Minangnese when they interacting with their peers from across tribes. In that situation, they choose to call themselves “Orang Pekanbaru” which means people who originated from Pekanbaru city instead. The study conducted on Minangnese students from Riau Islamic University (UIR) who were born and residing in Pekanbaru. Using snowball sampling and interview techniques researchers analyze their self-concept and the factors that influence it. This study concludes that the student’s self-concept dynamically changes throughout their development age. So, they see themselves Minangnese during their childhood era, then as they grow to teenage it turns into a negative feeling in the sense that he does not want to be considered a descendant of Minangnese, and later when they becoming a university student he starts to see himself as a Minangnese back with better perception. Some of the factors that influence them as teenagers are their view on the cultural gap among tribes in Pekanbaru, whereas the factors that make it changes again as students caused by the development of the mindsets.